Long-Run Purchasing Power Parity and the Dollar-Sterling Exchange Rate in the 1920's - Taylor, Mark (IMF Working Papers; Working Paper, 1990)
This paper replies to Ahking's (1990) re-examination of Taylor and McMahon's (1988) analysis of long-run purchasing power parity in the 1920s. We demonstrate that Ahking's conclusions are only partially correct and reestablish our conclusion that, a form of long-run purchasing-power parity did in fact hold for dollar-sterling during this period. The new results are also employed to gauge the degree of overvaluation of sterling relative to the imposed prewar parity of USD 4.86 upon its return to gold and for 12 months afterwards.